Question: Show that (ma,mb) = m(a,b) if m if greater than 0.

Answer: c = (a,b)

c = xa + yb

mc = mxa + myb = m(a,b)

This is where I'm stuck, I'm not sure how to prove that m(a,b) = (ma,mb). I also know that mc|ma and mc|mb.

Thanks!

Printable View

- December 10th 2007, 07:38 PMtemp31415gcd question
Question: Show that (ma,mb) = m(a,b) if m if greater than 0.

Answer: c = (a,b)

c = xa + yb

mc = mxa + myb = m(a,b)

This is where I'm stuck, I'm not sure how to prove that m(a,b) = (ma,mb). I also know that mc|ma and mc|mb.

Thanks! - December 11th 2007, 06:22 AMkalagota